METHODOLOGY FOR DEVELOPMENT OF PROFESSIONAL MOBILITY OF FUTURE VOCATIONAL EDUCATION TEACHER - Turabov Anvar Mavlankulovich (Galaxy International Interdisciplinary Research Journal, 2024)
The article analyzes different approaches to the phenomenon of professional mobility. An interpretation of personality development through a social movement is proposed. The methodology for the development of professional mobility of the individual is substantiated in the context of the subject-activity paradigm. The author concludes that the methodology for the development of professional mobility of a specialist presupposes the formation of his personality as a subject of professional activity. This is the process of developing a person’s internal creative potential for the implementation of his self-development and self-realization in accordance with emerging new social and professional tasks of varying levels of complexity.